EXAMINING CORRUPTION ISSUES IN MALAYSIA CONSTRUCTION INDUSTRY: PARTAKER PERSPECTIVES - Mohd Nordin, Rumaizah; Mohd Ahnuar, Ezlina; Md. Asrul Nasid Masrom, Md. Asrul Nasid Masrom; Naseem Ameer Ali, Naseem Ameer Ali (2023)
Unethical issues in relation to corruption is believed to slowly penetrate into the construction sector around the world due to its involvement with a multitude of players, different phases of work, and a great deal of input from both the public and private sectors. Due to the construction’s central role in development, corruption in construction can be harmful to the entire project mainly in terms of poor quality of the finished product, reduced economic return to investments, and increased number of injury and death. Despite concerns on this regard have been discussed, a commitment to rooting out corruption is crucial and is still unexplored. This paper aims to examine the homogeneity levels of perception between project stakeholders on the issues of corruption. A questionnaire survey was conducted with a total response of 37.6% was attained from the total of 189 questionnaires sent to the Government, public authorities, consultants, and contractors. The result indicates that there is a difference in perception between the different groups of respondents in the vulnerable areas of corruption in the construction project development. The outcome could be useful and pave a way for the policy maker in reforming anti-corruption strategies in order to mitigate corruption issues among construction industry players.